Pengaruh Kompetensi Dan Pemberian Insentif Terhadap Disiplin Kerja (Survei pada Karyawan Tasco Minimarket Tasikmalaya) - Anis Asma’uswatun Nisa; Askolani Askolani; Rita Tri Yusnita (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the effect of competence and giving of incentives on work discipline in Tasco Minimarket Tasikmalaya employees. The research method used is a quantitative method with a survey approach to 45 respondents, who are all employees at Tasco Minimarket Tasikmalaya. The type of data used is primary data. The data analysis technique used is multiple regression. The results of this test prove that competence and giving of incentives have a significant effect both partially and simultaneously on the work discipline of Tasco Minimarket Tasikmalaya employees.